Explorando novas possibilidades de formulações a partir do peeling de fenol com óleo de Croton tiglium (fórmula de Hetter) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
The demand for beauty and to mitigate the damage caused by aging and photoaging is constant. In this scenario, peeling procedures stand out for promoting skin regeneration by inducing an inflammatory process. The chemical peeling that uses phenol and Croton tiglium oil (OC) stands out for the good results generated. Despite its effectiveness, phenol has high toxicity and instability in these formulations. Thus, it’s important to propose the development of products that exploit the potential of OC and that are safer and more stable. In addition, with the discontinuation of Septisol® in 2019, it has been replaced by Novisol®, which left the formula more homogeneous. However, this important change in the composition of the formula brought the need for further studies. The present study proposed a preliminary evaluation of three approaches to formulations containing OC: replacement of phenol by chemical agents already used in peeling, with less toxicity (glycolic acid – AG – and trichloroacetic acid – ATA); administration of liquid crystals (LC) obtained from ternary systems (oleic acid/PPG-5-CETETH-20/water) to promote OC permeation; and assess the implications of changing OC concentration in formulas containing Novisol®. In the first approach, the formulations were prepared based on Hetter's formula, replacing phenol by AG or ATA. For the LC, from the ternary phase diagrams, with and without OC, 3 formulations of the cubic phase and 2 of the lamellar phase were selected. For Novisol®, the formulations were prepared based on Hetter's formula at concentrations of 0.8% and 2.4% of OC. To assess the approaches, an in vivo test (swine model) was performed, with biopsies performed at 1, 7 and 21 days after the treatments. Tissues were stained with Hematoxylin-Eosin and Herovici in order to evaluate histomorphometric components and differentiate collagen type I and type III, respectively. For the first approach, the formulation containing AG was inferior to the formulation containing ATA, which was possibly able to generate an inflammatory process on day 1 and also an increase in fibroblasts on day 21. It was possible to obtain LC in the proposed system, but they were not able to generate an inflammatory reaction in the dermis, suggesting that there was no permeation of the OC in the tested model. Formulations with Novisol® showed excellent results; all had an increase in cells on day 1, highlighting the formulation containing 2.4% of OC, which promoted a greater amount of collagen in 21 days after application. ATA stood out as a good chemical agent to be better explored in formulations with OC; CL require further studies to allow its use with the OC as active component; and formulation with Novisol® and 2.4% of OC stood out as the most promising alternative. Therefore, the present work leaves perspectives to be developed in three distinct approaches: ATA as a substitute for phenol with less toxicity, LC as systems that allow you to enjoy the benefits of OC for the skin and, especially, the advantages of using Novisol®, which provided superior results.
Keywords: ácido glicólico; ácido tricloroacético; peeling profundo; fenol; Croton tiglium; cristais líquidos; Novisol®; glycolic acid; trichloroacetic acid; deep peeling; phenol; Croton tiglium; liquid crystals; Novisol®; CNPQ::CIENCIAS DA SAUDE::FARMACIA